Crossbreeding between male pelung and female selected native chicken at second generation (G2) - Gunawan, Benny; Sartika, Tike (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Â  The experiment aimed to produce native chicken with faster growth rate that is to achieve body weight of more than 1 kg at 3 months of age. Three hundreds and thirty three crossbreeds (PK) day old chicken from the results of artificial insemination between male Pelung and second generation of selection of female native chicken, were used in this experiment. One hundred and eighty purebreds native chickens were also used as control population. They were put in grower cages with density of 10 birds per cage and each cage was treated as a single unit of replication. Feeds during experiment were given and divided into 3 phases that is Starter Feeds I (Protein 21% and Energy 3000 kcal/kg) for chicken between 0-21 days of age, Starter Feeds II (Protein 19% and Energy 2900 kcal/kg) for chicken between 22-42 days and Grower Feeds (Protein 17% and Energy 2900 kcal/kg) for chicken between 43-84 days. Variables which were recorded were weekly body weight until 12 weeks of age, feed consumption, feed conversion, mortality, carcass weight and simple economic ratio (B/C ratio). The results of the experiment showed that body weight at 12 weeks of crossbred (PK) was significantly higher than the pure native chicken (1000 vs 923 g) (P<0.05). Feed consumption was not significantly different (3037 vs 3036 g/bird/12 weeks), but the feed conversion of the crossbred was significantly better than the purebred (3.09 vs 3.4) (P<0.05). Carcass weight and carcass components were not significantly different between the two breeds, but they were different between sexes (P<0.05). Simple economic calculation showed that crossbreeds produced higher profit than purebreds with the benefit cost ratio were 1.31 for crossbred (PK) and 1.2 for purebred native chicken. The mortality rate during the experiment was low, that is 5.5% for crossbred and 6.36% for purebred. Â  Key words: Crossbreeding, male Pelung, female native chicken